Evaluation of Genetic Diversity among Proton Beam Induced Wheat Mutants through Trait Association and Multivariate Analysis - Bhagat, Twinkle Kumari; Das, Saikat; Mandal, Rupsanatan; Das, Bikram Kumar; Vishwakarma, Gautam (Journal of Cereal Research, 2023)
Mutation induction is a potential tool to create genetic variation in plants for crop improvement for novel traits which are not elsewhere existed in the available germplasm. Mutation induction has achieved great success in wheat breeding. Till date, 264 wheat varieties have been developed through mutagenesis. Among the physical mutagens, gamma rays were most widely used, however, it causes distant ionisation events resulting into spread out damage of DNA by the low linear energy transfer (LET) radiation. In contrast, proton beam which causes high linear energy transfer (LET) radiation, causes clustered damage in the DNA near the site of ionisation and produces a broad spectrum of variation. In the present study, wheat variety HI 1563 was mutated with 150 Gy proton beam (14 MeV) and subsequent mutant generations were grown at UBKV (M2 onwards) to assess the genetic variation among key morpho-phenetic traits. Considerable variation was observed for traits like DTH, PH, TPP, SL, SPP, TW, GYPP, BYPP and DTM in M3 generation. Trait association study indicated significant association between GYPP with other quantitative traits in the order of BYPP > PH > TPP > SPS > SL > TW > DTH > DTM. Cluster analysis revealed optimum number of 02 clusters where most of the early maturing plants with reduced height were grouped in Cluster I. PCA analysis revealed 03 PCs with Eigen values > 1.00 which contributed more than 65% of the total variation. PCA bi-plot indicated mutant lines with high cos2 values which were situated away from the origin included L1131, L1167, L1093, L1087, L1152, L297, L2536, L54, L1168, L1013, L228, L411, L412, L4638, L592, L675, L332, L424, L208, L209, L1065, L1170, L1180, L78, L1070, L1134 and L1042 and thus most divergent among the lot and could be selected for future breeding programme.